HUNGAN TINGKAT PENGETAHUAN PEMELIHARAAN KESEHATAN GIGI DAN MULUT DENGAN PENDIDIKAN IBU HAMIL DI KABUPATEN GIANYAR TAHUN 2021 - I G A Raiyanti; I Nyoman Gejir; Devi Kastini (Jurnal Kesehatan Gigi (Dental Health Journal), 2021)
The phenomenon in society was found, that 65% of pregnant women have four too high risk of pregnancy on dental health. This should be reduced by adequate prenatal care that focuses on health and reducing risk factors, so that these conditions can improve the outcome of pregnancy. The purpose of this study was to determine the relationship between the level of dental and oral health education on the knowledge of pregnant women at the KKN IPE location of the Health Poltekkes Denpasar Group 4 Gianyar I, Gianyar Regency in Sukawati and Ubud Districts in 2021. The research design used was an observational approach with a cross sectional design. The sample was carried out by accidental sampling with the research instrument in the form of an observation sheet with a total sample of 45 pregnant women. The results of the study of 45 respondents studied were mostly pregnant women with higher education as many as 23 (51.1%) and at least three with basic education. Based on the level of knowledge of pregnant women with the most in the good category, namely 27 people (60%) and the least with the less category, namely three people (6.67%). The average level of knowledge about dental and oral health care for pregnant women at the KKN IPE location of the Health Poltekkes Denpasar Group 4 Gianyar I Gianyar Regency in 2021 is 78.44 with sufficient category. From Spearman's rho analysis there is a significant relationship between education level and level of Education with a result of 0.064, this value 0.005. This means that there is a relationship between the level of education and knowledge . The conclusion is there is a relationship between the level of education and knowledge of pregnant women at the location of the IPE KKN Poltekkes Denpasar Health Ministry Group 4 Gianyar I Gianyar Regency in Sukawati and Ubud Districts in 2021